Компьютерный учебник по дисциплине «Компьютерные технологии конструкторского проектирования» - Свидерская, Л. И.; Рыбка, Д. С.; Зайцев, С. А.; Немцев, B. C. (УАДО, 2002)
In paper the system of remote tutoring on discipline " Computer techniques of designer projection " is considered. The exposition of such known packets as AutoCAD 2000, P-CAD 4.5, Electronic Work Bench and ACCEL EDA has come in a structure of a system. The system powers up the integrated environment and allows to conduct all aspects lessons: a lecture material, practical occupations, has a monitoring system of knowledge and set of the personal jobs (definitions)
Keywords: компьютерный учебник; конструкторское проектирование